1993
DOI: 10.1159/000236564
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Proliferation Induced by Pertusis Toxin Utilizes a Pathway Parallel to Transforming Growth Factor-Beta-Sensitive Growth

Abstract: Pertusis toxin (PTX) has been shown to potentiate autoimmunity in experimental autoimmune disease. The exact mechanism of this effect has not been determined; however, the modification of G proteins by ADP-ribosylation has been suggested. Here it is demonstrated that this modification may contribute to autoimmunity by the abrogation of transforming growth factor-β (TGF-β) growth-inhibitory signals. Anti-TGF-β demonstrated the same effect on lymphocytes as high concentrations of PTX in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Studies in the mouse using ZP3 peptide has suggested that cytotoxic T cells may be involved in oocyte damage [Rhim et al, 1992;Lou and Tung, 1993]. Many of these studies have utilized the pertussis toxoid in foot pad injections which has been shown to be a molecular mimic that itself induces autoimmune disease [Cronkhite, 1993;Sudweeks et al, 1993;Ryan et al, 1998], making this a complicated model system to study ZP immune response. However, Paterson et al [1998] have demonstrated suppression of fertility in marmosets that were administered with human ZP3 peptide immunogen without any effect on follicular development.…”
Section: Effect Of Antibodies Against Zp Proteins On Ovarian Folliculmentioning
confidence: 99%
“…Studies in the mouse using ZP3 peptide has suggested that cytotoxic T cells may be involved in oocyte damage [Rhim et al, 1992;Lou and Tung, 1993]. Many of these studies have utilized the pertussis toxoid in foot pad injections which has been shown to be a molecular mimic that itself induces autoimmune disease [Cronkhite, 1993;Sudweeks et al, 1993;Ryan et al, 1998], making this a complicated model system to study ZP immune response. However, Paterson et al [1998] have demonstrated suppression of fertility in marmosets that were administered with human ZP3 peptide immunogen without any effect on follicular development.…”
Section: Effect Of Antibodies Against Zp Proteins On Ovarian Folliculmentioning
confidence: 99%
“…pertussis infection or administration of a whole-cell based B. pertussis vaccine have been shown to induce Agspecific IFN-γ production from both CD4 + and CD8 + T cells and Th1 responses in infants [62]. Indeed, PTX has been widely used to induce Th1-mediated organ-specific experimental autoimmune (EA) diseases in animal models, including murine encephalomyelitis (EAE), orchitis and uveitis (EAU) [63][64][65][66][67][68][69]. In particular, EAU was shown to be mediated by the expression of IFN-γ from PTX-stimulated dendritic cells (DC) [39], although transfer of lymphocytes from PTX-treated donor mice could cause this disease [70].…”
Section: Ptx/ptx-b Modulation Of Autoimmune Responsesmentioning
confidence: 99%